Análisis del gasto público del Presupuesto General del Estado en el sector salud de Ecuador - León Guerrero, Joel Genaro (2022)
The topic presented on public spending particularly, in the Health sector, covers, of course, national territoriality based on macroeconomic indicators that were selected; then it is conceived to have reached the objective of analyzing the public expenditure of the General State Budget in the Health sector of Ecuador, a sector for which the designated resources must have a marked priority since it is about human development, therefore social. The methodology used was predominantly quantitative and certain qualitative positions, with a descriptive and explanatory scope, through the collection of statistical information from different accredited bodies. From the analysis, the regularities referring to an approximately stable planning of the General State Budget during the period 2016-2021 were obtained, even when the effects in the initial and final years are visualized due to the variations in total expenses due to the unexpected appearance of the natural disaster such as the earthquake in 2016 and the COVID-19 pandemic that reached its greatest crisis in 2020. Likewise, the expenditures of the budget designated for health in the period showed that the percentages of execution of these assigned expenses maintain approximate levels; but the ratio, share of accrued expenditure on health over GDP values reflects that the rules of dedicating 4% of GDP amounts to health are not met. The importance of the study lies precisely in the fact that it exercises economic analysis focusing on the development of people.